Enhancing sustainability in CFRP with a solvent-free, fully closed-loop recyclable bio-based epoxy vitrimer - Lee, Jae Hoon; Kim, Yong Min; Kim, Wonbin; Song, SeungHyeon; Choi, Junseok; Kim, Eunjung; Kim, Sarang; Park, Hyungbum; Yu, Woong-Ryeol; Na, Wonjin; Choi, Yong-Seok (Pergamon Press Ltd., 2026)
We propose a fully closed-loop recyclable vanillin-based epoxy vitrimer (IAIE) to enhance the sustainability of carbon fiber-reinforced polymers (CFRPs). IAIE is synthesized via a solvent-free process by curing a liquid-phase imine-containing vanillin-based epoxy (IE) with a liquid-phase imine-containing diamine (IA), both of which are specifically designed in liquid form to facilitate their direct use as matrix components in CFRP fabrication. Owing to the rapid dynamic imine exchange, IAIE demonstrates superior properties, including enhanced toughness (49.7 MJ/m3), self-healing ability, and excellent reprocessability. Closed-loop recycling is achieved through dynamic imine exchange: IAIE is degraded in the presence of excess liquid-phase IA monomer at 60 degrees C without using solvents, and is subsequently re-cured by adding a stoichiometrically equivalent amount of IE. IAIE imparts notable improvements to CFRPs, including distinctive plastic deformation, increased fracture toughness (99.8 kJ/m2), and enhanced interlaminar shear strength (18.3 MPa). Importantly, the interface between carbon fibers and the IAIE resin in delaminated CFRPs can be repeatedly healed through mild heating, demonstrating a level of reprocessability that has previously been considered impractical for CFRPs. Furthermore, the IAIE resin can be selectively removed through chemical recycling, with the reclaimed carbon fibers preserving their surface morphology and mechanical modulus. These findings underscore the potential of IAIE as a sustainable, highperformance matrix for composite applications. This innovative vitrimer system offers an effective pathway toward reducing the environmental footprint of CFRPs by enabling material reuse and minimizing composite waste.